2015
DOI: 10.1111/febs.13209
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA‐30a inhibits hepatitis B virus X protein‐induced autophagosome formation in hepatic cells

Abstract: Hepatitis B virus (HBV) enters the host and survives by using several mechanisms. One of the ways that HBV survives and replicates in the host cells is by inducing autophagy. Previous reports have shown that microRNA (miRNA)-30a inhibits autophagosome formation in cancer cells. Hence, we hypothesized that overexpression of miRNA-30a could inhibit HBVinduced autophagosome formation in hepatic cells. To study this, both HepG2 cells and HepG2.2.1.5 cells (HBV-expressing stable cell line) were transfected with miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…Previous studies have shown that miRNA-30a inhibits autophagy in ischemic stroke, cardiomyopathy and some carcinomas by downregulating Beclin-1 expression (Zhu et al, 2009;Zou et al, 2012;Yin et al, 2013;Pan et al, 2013;Wang et al, 2014;Yu et al, 2012). Recently, a report by Kumar et al demonstrated that miR-30a was involved in modulating autophagosome formation induced by Hepatitis B virus X protein (HBx), and that this effect was mediated via reduced Beclin-1 expression (Kumar et al, 2015). Our data showed that miR-30a was downregulated by EV71-induced autophagy mediated by Beclin-1 and further demonstrated that Beclin-1 contains a potential binding site for miRNA-30a.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miRNA-30a inhibits autophagy in ischemic stroke, cardiomyopathy and some carcinomas by downregulating Beclin-1 expression (Zhu et al, 2009;Zou et al, 2012;Yin et al, 2013;Pan et al, 2013;Wang et al, 2014;Yu et al, 2012). Recently, a report by Kumar et al demonstrated that miR-30a was involved in modulating autophagosome formation induced by Hepatitis B virus X protein (HBx), and that this effect was mediated via reduced Beclin-1 expression (Kumar et al, 2015). Our data showed that miR-30a was downregulated by EV71-induced autophagy mediated by Beclin-1 and further demonstrated that Beclin-1 contains a potential binding site for miRNA-30a.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of miR-22 premiRs, anti-miR-22 oligos or non-specific miRNA (NS) (Sigma-Aldrich, St Louis, MO, USA) was performed using siPORT™ NeoFX™ transfection reagent (Thermofisher, Carlsbad, CA, USA) as described by us previously [17]. After the experiments, the cells were collected for either total RNA isolation or protein separation.…”
Section: Methodsmentioning
confidence: 99%
“…The Atg family of proteins is critical for autophagy. Several of them, Atg4, Beclin‐1 and LC3, have been shown to be the targets of miRNAs such as miR‐30a and miR‐204, suggesting that miRNA can regulate autophagy. Here, we show that HBV levels are inversely correlated with the levels of cellular miRNA miR‐192‐3p in HBV patients as well as in cultured cells.…”
mentioning
confidence: 99%